2015
DOI: 10.3109/00498254.2015.1016136
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of pharmacophore and VolSurf models to predict the substrates of UDP-glucuronosyltransferase1A3

Abstract: 1.UDP-glucuronosyltransferase1A3 (UGT1A3) catalyzes glucuronidation of numerous xenobiotics/drugs. Here, we aimed to establish substrate selectivity models for UGT1A3 using the pharmacophore and VolSurf approaches. 2.Fifty structurally diverse substrates of UGT1A3 were collated from the literature. These substrates were divided into training (n=34) and test sets (n=16). The pharmacophore model was developed using the Discovery Studio 2.5 software. A user-defined feature (i.e. the glucuronidation site) was incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The pharmacophore model indicated that hydrogen-bonding acceptor played a significant role for the molecules glucuronidation by UGT1A8, consisting with the results of pharmacophore analysis for UGT1A3 and UGT2B7 [19,20]. Hydrogen-bond acceptor was regarded as a hydrophilic group.…”
Section: Discussionmentioning
confidence: 92%
“…The pharmacophore model indicated that hydrogen-bonding acceptor played a significant role for the molecules glucuronidation by UGT1A8, consisting with the results of pharmacophore analysis for UGT1A3 and UGT2B7 [19,20]. Hydrogen-bond acceptor was regarded as a hydrophilic group.…”
Section: Discussionmentioning
confidence: 92%
“…The same group have recently developed very similar VolSurf‐3D QSAR and Pharmacophore‐3D QSAR models for estimating clearance of UGT1A3 substrates . This study used a dataset of 34 compounds in the training set and 16 compounds in the test set for which clearance data were collected from the literature reports on recombinant enzyme.…”
Section: Prediction Of Phase II (Ugt and Non‐ugt) Drug Metabolismmentioning
confidence: 99%
“…The same group have recently developed very similar VolSurf-3D QSAR and Pharmacophore-3D QSAR models for estimating clearance of UGT1A3 substrates. 143 This study used a dataset of 34 compounds in the training set and 16 compounds in the test set for which clearance data were collected from the literature reports on recombinant enzyme. Using a very similar methodology, they found that the test set prediction accuracies for 81% of the UGT1A3 substrates prediction were within one log unit for a four-log unit range.…”
Section: Ugt2b7mentioning
confidence: 99%